Tinjauan Teologis Tentang Api Penyucian dalam Ajaran Katolik Roma Didasarkan Pada Kebenaran Alkitab dan Implikasinya Bagi Kehidupan Orang Percaya - Ijen, Ijen; Moro, Agus Ndara Manu (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2021)
Purgatory is a state, place of purification or temporary punishment. According to Catholic teaching, purgatory refers to a state, or place, where the soul of the dead is purified. There, it is cleansed of unpardonable sin. However, the teaching of purgatory has no place in Christian theology. Therefore, the purpose of writing this scientific work is to explain and describe the theological review of purgatory in Roman Catholic teaching based on biblical truth and implications for the lives of believers. The author uses a qualitative method with a literature study approach. The discussion in this study shows that only the blood of Jesus can erase and purify humans and nothing else. Everyone who lives in Christ will not experience condemnation.